IITA Documentary - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
IITA is Africa's leading partner in agricultural transformation. For more than 50 years, IITA and its partners have supported smallholder African farmers in addressing the challenges of tropical agriculture.